Combination of Screen-Printed Carbon Electrode and Molecularly Imprinted Polymers for the Selective Determination of Phenolic Compounds in Wine - Marie Elhachem; Elias Bou-Maroun; Maher Abboud; Richard G. Maroun; Philippe Cayot (MDPI AG, 2022)
Caffeic acid (CA) is an efficient antioxidant found in wine and in plants and can be extracted from the by-products of the food industry. A molecularly imprinted polymer specific to caffeic acid (CA-MIP) was prepared by radical polymerization using N-phenylacrylamide as the functional monomer, ethylene glycol dimethacrylate as the cross-linker, and azobisisobutyronitrile as the initiator, in the presence of CA as the template molecule. The rebinding activities between the polymers and CA were promoted by an indirect method and characterized by cyclic voltammetry (CV) using a screen-printed carbon electrode (SPCE). It is a fast method, which only requires simple and portable instrumentation. The polymer showed a high selectivity toward CA and a good repeatability. CA-MIP was then applied in wine samples spiked with CA, and the results were compared to those obtained by a chromatographic method. With a limit of detection of 0.06 mM in wine, the recovery values confirmed that the method is suitable for further applications.